Gift - Garwood, Julie (New York : Pocket Books, 1991)
A child bride and charming innocent, Sarah Winchester has dismissed the ancient feud that divided her fiance's family from her own, and she was totally unaware of his past as the notorious pirate, Pagan. Nathan had never bared his soul to any woman, but he was soon utterly beguiled and exasperated by Sara's sweet defiant ways. A conspiracy to tear them apart leaves their future at stake.
Keywords: Pirates -- England -- 19th century; Man-woman relationships -- England -- 19th century; England -- Social life and customs -- 19th century; Love stories; Historical fiction